Pengaruh Penerapan Model PjBL Berbantuan Media Video Terhadap Hasil Belajar Subtema Manusia dan Lingkungan - Rabiatul Adawiah Pulungan; Irvan Permana; Yuli Mulyawati (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
One of the efforts made to overcome the low learning outcomes is the selection of the right learning model. The purpose of this study was to determine the application of the Project Based Learning model and its effect on human and environmental sub-themes learning outcomes for class V SDN Ciomas 04. This research approach was quantitative, the type of experimental research was quasi-experimental design. This research is located at SDN Ciomas 04. The population of class V SDN Ciomas 04 Bogor regency is 31 students. The Data collection techniques: tests, observations and documentation. Data analysis techniques: Descriptive and inferential statistics. Independent sample T-Test hypothesis test. The results showed that the application of the Project Based Learning model could be carried out well based on the stages of learning. The results of the study showed that the average value in the experimental group was higher than the control group. There is an effect of the Project Based Learning model on the human and environmental sub-themes learning outcomes of fifth grade students of SDN Ciomas 04 based on the analysis test stating that the t-count value is greater than the ttable value.